Integration of Ngumbai Lawok Culture and Language in Learning to Develop Social-Emotional Interaction Using Image Media for Early-Age Children - Khasanah, Uswatun; Srisusilawati, Eneng; Ruiyat, Suci Aprilyati; Fajarianto, Otto (JTP - Jurnal Teknologi Pendidikan, 2024)
The social and emotional growth of young children is significant for fostering empathy, communication, and social interaction. However, education in schools often ignores the linguistic and cultural components around children, thereby hampering the development of some parts of their social-emotional relationships. The ngumbai lawok tradition is one of the cultures of Lampung's coastal communities in appreciating marine products which can be integrated with language to improve children's social and emotional development using image media. This research aims to find out how early childhood learning that combines Ngumbai Lawok language and culture using image media can influence the formation of social and emotional relationships in early childhood. This research methodology is an action research design that combines qualitative and quantitative techniques. The research subjects are children aged 3-6 years at the early childhood education institution in Batanghari sub-district, East Lampung. Data is collected through observations, instructor interviews, questionnaires, documentation to measure children's social and emotional growth, and records of social-emotional development activities. Data analysis includes quantitative and qualitative to compare changes in children's social and emotional development before and after intervention. Research shows that the Numbai Lawok language and culture combined with image media can improve children's ability to interact socially and emotionally. The use of image media helps children understand the cultural concepts of Numbai Lawok and stimulates their language development, and children show improvements in aspects of cooperation, empathy, and communication. This research concludes that the integration of local culture and language with visual media is effective in improving the social emotional skills of young children.